Role of Ureteric DJ Stenting Following Ureteroscopic Removal of Stone with Pneumatic Lithoclast for Mid and Lower Ureter Stones - Ansari, Wesh; Dhakal, Prakrit; Bogati, Ananya Singh (Nepal Medical College Journal, 2024)
It is traditional way to place DJ stent following ureteroscopic removal of stones (Ureterorenoscopy lithotripsy). DJ stenting prevents formation of stricture in ureter and has a protective function on kidney/ ureter. However use of DJ stent can result in pain and lower urinary tract symptoms (LUTS). There is no consensus on placing a ureteral catheter after uncomplicated ureteroscopy and it is still controversial. A cross sectional observational study was conducted in Urology Department of Nepal Medical College Teaching Hospital, Attarkhel, Kathmandu from 1st January 2024 to 31st July 2024. The purpose of this study was to see the role of DJ stenting in patients undergoing intra- corporeal pneumatic lithotripsy for mid and distal ureteric stone. Along with VAS SCORE (Pain) post-operative, need for analgesic, stone clearance and complications following pneumatic lithotripsy. A total 64 patients were included in our study. They were randomly allocated to two groups; A and B. Group A included all patients with DJ stent (6 FR) and group B include patients without DJ stents. Post-operative care was carried out for about 24 to 48 hours. Oral analgesic 50 mg Diclofenac was given as per need. All the patients were followed up at the interval of week 1st, 4th, 8th and 12 th week. The outcomes were measured on the basis of postoperative pain, analgesic dose and stone clearance at the end of the study. Mean of post-operative pain at 12th week was 5.93 in group A and 1.06 in group B. Stone clearance in group A was 81.3%, and group B was 75%. Use of additional analgesia in group A shows 34.4% and 18.8% in group B, P value was 0.157.